Analyzing the Most-Favored Nation Treatment Principle: A Study of Malaysia’s Bilateral Investment Treaties and Their Implications - Mohammad Belayet Hossain (APPTHI, 2025)
This study critically examines the application of the Most-Favoured Nation (MFN) treatment principle within Malaysia’s Bilateral Investment Treaties (BITs) and its broader implications for investment governance. Drawing from doctrinal legal analysis and expert interviews, including insights from Professor Zakiri of Universiti Utara Malaysia, the research explores how MFN clauses influence Foreign Direct Investment (FDI), investor-state relations, and Malaysia’s regulatory sovereignty. The findings reveal significant inconsistencies and ambiguities in the interpretation of MFN clauses-particularly concerning their applicability to procedural rights such as dispute settlement. These gaps not only risk treaty shopping but also constrain Malaysia’s ability to enact public interest regulations in areas like health, environment, and taxation. The study recommends the development of a Model BIT that includes clearly defined MFN scopes, sustainable development carve-outs, and alignment with ESG principles. It advances the ongoing discourse on how to balance investor protection with space policy and provides practical suggestions for reforming Malaysia’s international investment treaty framework.